Strategies of market segmentation and segment targeting - Stahurska, Svitlana; Tkachuk (Stakhurska), Svitlana (My University, 2016)
The paper examines different approaches to market segmentation and segment targeting strategies development, based upon the complex set of psychological, social and other factors.
Keywords: market segmentation; segment targeting; factors of segmentation; сегментація ринку; фактори сегментації; кафедра економіки праці та менеджменту; кафедра маркетингу